Healing of dehiscence defects following root surface demineralization with tetracycline: A histologic study in monkeys - Nagata, MJH; Bosco, Álvaro Francisco [UNESP]; Leite, C. M.; Melo, LGN; Sundefeld, MLMM (Amer Acad Periodontology, 2005)
Background: the purpose of this study was to histologically evaluate the healing of experimental dehiscence defects after surface demineralization with tetracycline hydrochloride.Methods: Six adult male monkeys (Cebus apella) were used in this study. Dehiscence defects were surgically created on the buccal aspect of the mandibular lateral incisors in all animals. The root surfaces were debrided and planed. In a split-mouth design, a 10% tetracycline hydrochloride solution was applied to one tooth for 4 minutes (T group), followed by irrigation with saline. The contralateral tooth served as a control (C group). The flaps were repositioned and sutured. The animals were sacrificed at 6 months postoperatively and histological sections were processed. Computer-assisted histomorphometric analysis was used to evaluate the formation of new cementum, new bone, new connective tissue attachment, and length of the epithelium (junctional and sulcular).Results: Bone regeneration was similar in both groups (1.5 +/- 0.3 mm for the T group and 1.5 +/- 0.6 mm for the C group). The C group showed more new cementum than the T group (2.3 +/- 0.3 mm versus 2.2 +/- 0.3 mm) as well as a longer epithelium (1.0 +/- 0.3 mm versus 0.9 +/- 0.2 mm). The T group presented more new connective tissue attachment (3.1 +/- 0.2 mm) than the C group (2.9 +/- 0.6 mm). However, no statistically significant differences were detected between the two groups.Conclusions: the amount of new attachment was similar in both groups. Root conditioning with 10% tetracycline solution did not produce any additional new attachment in comparison to the controls.
Keywords: animal studies; bone, demineralized; periodontal attachment; periodontal regeneration; tetracycline/therapeutic use; tooth/anatomy and histology